Digital prototyping, open design, and sustainability in industrial design education: a case study. Issue 1 (2nd January 2023) - Kucuksayrac, Elif
ABSTRACT: This study investigates digital prototyping in undergraduate industrial education through a case study of two pilot projects and a new elective and project-based course. It explores the literature on digital prototyping, open design, and sustainability, analyses student projects through the case study, and discusses the findings in relation to the literature review. In the study, two frameworks are suggested that aim to guide digital prototyping education in the industrial design field. The first framework aims to frame the content, and the second seeks to frame the context for the student projects. The first framework focuses on the relationship between the completeness of the products when they meet the users, the level of users' design skills, and possible user-intervention types to the product. The second framework focuses on environmental and economic sustainability, considering the benefits and risks of four possible scenarios according to the user-engagement type.